2012
DOI: 10.1002/nml.21064
|View full text |Cite
|
Sign up to set email alerts
|

Running on Empty: The Operating Reserves of U.S. Nonprofit Organizations

Abstract: Operating reserves allow nonprofit organizations to smooth out imbalances between revenues and expenses, helping to maintain program output in the presence of fiscal shocks. We know surprisingly little about why nonprofits might save operating reserves and what factors explain variation between organizations' savings behavior. Findings suggest that operating reserves are reduced in the presence of concentrated public funds, access to debt, fixed assets, and endowment. However, size is not an important predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
2
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 22 publications
4
92
2
4
Order By: Relevance
“…Few studies appear to have considered expenses of nonprofit organizations (Wicker & Breuer, 2011 A recent large-scale study on German and Swiss nonprofit sport organization indicated increased organizational size was also associated with increased expenses and thus did not reduce the organization's financial challenges . These findings are further supported by Calabrese's (2013) discovery of the lack of influence of organizational size as a predictor of operating reserves among nonprofit organizations.…”
Section: Volunteer Motivessupporting
confidence: 66%
“…Few studies appear to have considered expenses of nonprofit organizations (Wicker & Breuer, 2011 A recent large-scale study on German and Swiss nonprofit sport organization indicated increased organizational size was also associated with increased expenses and thus did not reduce the organization's financial challenges . These findings are further supported by Calabrese's (2013) discovery of the lack of influence of organizational size as a predictor of operating reserves among nonprofit organizations.…”
Section: Volunteer Motivessupporting
confidence: 66%
“…Any quantitative empirical study where clustering or contagion could be at play should lead us to test for spatial dependence. Valuable datasets such as the NCCS core files could exhibit spatiality: studies of financial distress (Never 2014;Hager 2001), financial reserves (Calabrese 2013), market entrance (Mook, Maiorano, and Quarter (2015), voluntarism (Rotolo, Wilson, and Dietz 2015), and donative behavior (Casale and Baumann 2015), all could have clustering of like organizations. Clustering and contagion can also be prevalent in studies of resource flows across actors, where space is more conceptual than physical geography Hays 2006, Frazese, Robert, andHays 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, state and local tax exemptions also encourage nonprofit charities' capital formation. Because much of nonprofit charities' capital takes the form of fixed assets (Calabrese, 2013), this tax exemption is especially valuable at the state and local levels because of the variation in types and effective rates of taxes imposed upon these types of assets. In addition to income tax exemptions, registered nonprofit charities are usually exempt from sales taxes that are levied at the state level, as well as property taxes at the state and/or local level.…”
Section: Nonprofit Charities Tax Exemptions and Rent-seekingmentioning
confidence: 99%